2017
DOI: 10.1080/09638288.2017.1410583
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and interpersonal effects of coping on the psychological well-being of adults with sensory loss and their spouses

Abstract: The results highlight the need to support the well-being of adults with sensory loss and their spouses in rehabilitation, and the importance of both intra- and interpersonal coping in the adjustment process. Implications for rehabilitation Rehabilitation specialists and social workers working with adults with sensory loss should, where possible, incorporate family members into support plans. Rehabilitation specialists and social workers working in sensory rehabilitation should be mindful of how the coping styl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 55 publications
3
12
0
4
Order By: Relevance
“…Similarly, the same trend was observed in a longitudinal study of people with sensory loss (hearing or vision) (Lehane, Dammeyer, & Wittich, 2017). They found that avoidant or distraction-based coping strategies was deleterious to psychological well-being, while those with an active and more accepting coping style fared better.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Similarly, the same trend was observed in a longitudinal study of people with sensory loss (hearing or vision) (Lehane, Dammeyer, & Wittich, 2017). They found that avoidant or distraction-based coping strategies was deleterious to psychological well-being, while those with an active and more accepting coping style fared better.…”
supporting
confidence: 68%
“…This gives weight to the argument that the detrimental impact of hearing loss on an individual can to a certain degree be modified by how the affected person perceive the hearing loss as an hindrance and what coping behaviours are used (Gomez & Madey, 2001;Lehane et al, 2017). This phenomenon has also, to varying degrees, been observed in chronic pain research, which is a field where much of the development of acceptance as a key concept in living with a chronic condition has taken place (McCracken, 1998;Viane et al, 2003).…”
Section: Figure 1correlational Heat Map Of All Items On the Haqmentioning
confidence: 96%
“…First, with regard to mean differences across each of the measures, spouses reported a greater level of acceptance of the sensory loss than AWSLs, AWSLs reported greater perceived partner acceptance, and AWSLs reported greater psychological distress. Although sensory loss has a demonstrated effect on spouses’ well‐being (e.g., Lehane, Dammeyer, & Elsass, ), these results indicate that, as the individual with the disability, AWSLs may have a greater need for support to be able to reach a state of acceptance and positive adjustment.…”
Section: Discussionmentioning
confidence: 91%
“…Survey data were collected as described by Lehane, Dammeyer, and Wittich (2017). Specifically, the project was advertised using a variety of online media including Facebook (advertising, project page, group posting), Twitter, Instagram (project page, advertising), Reddit, a project website, and professional e-mail lists.…”
Section: Methodsmentioning
confidence: 99%